Compatibility promotion between platforms: The role of open technology standards and giant platforms - Sebastian Spaeth; Sven Niederhöfer (Electronic Markets, 2022)
Most platform literature focuses on single platforms and their governance, e.g. concerning app developers. Yet, platform competition and dynamics are increasingly important as they form connections with each other and build complex networks. More focus on platform-to-platform relationships and the role of standards is warranted. Therefore, the goal of this study is to investigate how platform sponsors select platforms to promote as compatible with their own products, taking open standards and "giant platforms" into account. To address these questions, we construct a unique data set covering 157 platforms in the smart home market. We conduct a network analysis based on an exponential random graph model (ERGM) to incorporate platform features, dyadic characteristics, and structural processes. We find that platform-to-platform compatibility promotion is determined by a careful selection of platforms with dissimilar industry sectors and ecosystem niches. We identify two strategic approaches to select and promote platforms as compatible, based on standard complementarity and the size of the installed base. We find that platforms more often promote other platforms with similar supported standards. The majority of endorsements are directed at giant platforms, allowing platforms to support a smaller number of standards and thus a reduced degree of openness at the technology level. Platforms often integrate several giant platforms at the same time. Our study makes two major contributions to the literature. First, we extend the concept of selective promotion (Rietveld et al. 2019) to include inter-platform compatibility and open technology standards. Second, we demonstrate how platform sponsors compensate for higher accessibility at the technology level with transparency at the marketplace level.
Keywords: M31; 620; Platforms; Ecosystems; Standards; Openness; Competition; Internet of things